ANALISIS NILAI MORAL PADA ANTOLOGI CERPEN INSPIRATIF “18 CERITA MENGGUGAH” KARYA RORA RIZKY WANDINI, DKK - Agnes Endwitri Sihombing; munthe, dila (FKIP, Universitas Palangka Raya, 2023)
Moral values ​​in literary works in the form of short stories usually reflect the views of the author concerned about moral values. Learning about morals can be obtained from the literary works we read. The purpose of this study is to reveal and examine the moral values ​​contained in a short story. This research is a document analysis research in the form of literature study. The type of research used in this research is descriptive research. The collected data is analyzed, identified, classified and described. The source of data in this research is a literary document in the form of an anthology of inspirational short stories